2003
DOI: 10.1128/aem.69.11.6659-6668.2003
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Structure in Midgut and Hindgut of the Humus-Feeding Larva of Pachnoda ephippiata (Coleoptera: Scarabaeidae)

Abstract: The guts of soil-feeding macroinvertebrates contain a complex microbial community that is involved in the transformation of ingested soil organic matter. In a companion paper (T. Lemke, U. Stingl, M. Egert, M. W. Friedrich, and A. Brune, Appl. Environ. Microbiol. 69:6650-6658, 2003), we show that the gut of our model organism, the humivorous larva of the cetoniid beetle Pachnoda ephippiata, is characterized by strong midgut alkalinity, high concentrations of microbial fermentation products, and the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
185
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(193 citation statements)
references
References 58 publications
5
185
1
2
Order By: Relevance
“…Most of the data obtained on insect gut bacterial diversity is derived from traditional microbial methods such as viable plate counts and phenetic taxonomy. However, in recent years the use of the rRNA approach enables further characterization of the enteric microbiota of many insects (Egert et al, 2003;Reeson et al, 2003;Dillon and Dillon, 2004;Behar et al, 2005;Capuzzo et al, 2005;Mohr and Tebbe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the data obtained on insect gut bacterial diversity is derived from traditional microbial methods such as viable plate counts and phenetic taxonomy. However, in recent years the use of the rRNA approach enables further characterization of the enteric microbiota of many insects (Egert et al, 2003;Reeson et al, 2003;Dillon and Dillon, 2004;Behar et al, 2005;Capuzzo et al, 2005;Mohr and Tebbe, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The high alkaline pH in the gut of lepidopteran insects could kill many microorganisms. However, alkaline conditions favor the dominance of Firmicutesrelated bacteria in the midgut of the beetle Pachnoda ephippiata [134]. Both culture-dependent and culture-independent methods have detected the presence of Enterococcus in the alkaline midgut of the gypsy moth larva [135].…”
Section: Discussionmentioning
confidence: 99%
“…GHGs production per kg of mass gain from three insect species such as mealworm larvae, crickets and locusts studied by Oonincx et al, (2010), revealed that all three insect species produce less GHGs as well as ammonia compared to per kg of mass gain from pigs and beef cattle. Insect species such as termites, cockroaches and scarab beetles produce methane due to the bacterial fermentation (Hackstein and Stumm, 1994;Egert et al, 2003). However insect species such as mealworms, crickets and grasshoppers which are economically suitable for mass production has less GHGs production characters remains the viable options for producing alternate food source.…”
Section: Production Of Greenhouse Gasesmentioning
confidence: 99%